Polyethylene Glycol Mediated Kinetic Study of Nitro Decarboxylation of α,β-Unsaturated Acids by Blau’s Fe(III) Phen Complex - K. Ramesh; S. Shylaja; K. C. Rajanna; P. Giridhar Reddy; P. K. Saiprakash (Journal of Chemistry)
Polyethylene glycol (PEG) mediated kinetic study of nitro decarboxylation of α,β-unsaturated acids (USA) has been taken up by Blau’s [Fe(III) nitrate-Phen] yellow complex in acetonitrile medium. Kinetics of the reactions indicated Michaelis-Menton type of mechanism and rate law. Reaction rates are significantly influenced by the structural variation and concentration of PEG. Catalysis of PEG was explained on the lines of nonionic micelles such as TX-100 because of their structural resemblance and also due to a slight negative charge developed on polyoxyethylene and cationic form(s) of Fe(III) chelates in the intermediate stages.